How to treat patients with chronic insomnia? The contribution of clinical psychology - Clemente, Vanda (2006)
Insomnia is a chronic health problem extremely prevalent and severe impairment of quality of life. Despite scientific advances, many patients remain without adequate treatment. This article presents the factors and psychological mechanisms that make chronic insomnia clinical entity is autonomous and described the contribution of insomnia in clinical psychology through the cognitive-behavioral intervention.